Building a Winning Team: PT XYZ’s Approach to Optimizing Performance through Discipline and Culture - Mutmainah , Mutmainah (Dinasti Publisher, 2024)
This study aims to analyze the influence of work discipline and organizational culture on team performance at PT XYZ. Work discipline is considered a major factor in creating high productivity through compliance with company rules, punctuality, and individual responsibility in completing tasks. Meanwhile, organizational culture plays a role in forming a positive work environment, increasing employee engagement, and strengthening loyalty to the company. This study uses a quantitative method with a descriptive correlational approach. The research sample consisted of 150 respondents selected from a population of 300 employees using a proportional random sampling technique. Data collection was carried out through a questionnaire that had been tested for validity and reliability, and analyzed using multiple linear regression. The results showed that work discipline had a positive and significant influence on team performance with a value of t = 6.78 and p = 0.000. Organizational culture was also proven to have a significant influence on team performance with a value of t = 5.92 and p = 0.001. Simultaneously, work discipline and organizational culture had a significant influence on team performance with a value of F = 24.67 and p = 0.000. These findings indicate that the combination of high work discipline and strong organizational culture is an effective strategy in building a superior team at PT XYZ. The implications of this study indicate that companies need to strengthen clear and consistent work discipline policies, as well as create an organizational culture that supports innovation, open communication, and team collaboration in order to improve overall performance. Thus, a human resource management strategy that focuses on the balance between work discipline and organizational culture can be a solution to improve the company's competitiveness in the long term.